IT consultant : a commonsense framework for managing the client relationship - Freedman, Rick (Jossey-Bass Pfeiffer San FranciscoUS, 2000)
Targets the IT professional who is considering a career in IT consulting; as well as the professional consultant who is seeking to upgrade his skills. Provides an overview of the profession of consulting and identifies technical, business and communication skills as the consulting skill set. Presents the IT consulting framework, using topics including: negotiating the relationship; understanding the client's situation; and delivering business results. Discusses how to develop superior consulting skills; and provides various sample materials in the appendices.